Ethnomathematical Concepts in the Minangkabau Traditional Game ‘Pistol-Pistolan’: An Ethnographic Study - Isnaniah Isnaniah; M. Imamuddin; Muhammad Mutawakil Amr (AL-ISHLAH: Jurnal Pendidikan, 2026)
Ethnomathematics research in Minangkabau is still dominated by studies of static cultural artifacts, while traditional children's games that are constructive and involve motor activities have not been widely researched. This study aims to identify mathematical concepts in the traditional game of “Pistol-pistolan”, which is made from banana leaves. The research used a qualitative approach with ethnographic methods and was conducted in Bukittinggicity, West Sumatra. Data were collected through participant observation, visual documentation, and semi-structured interviews with elementary school-aged children as players, lecturers and teachers of Minangkabau Natural Culture. The results of the study show that the structure of the pistol-pistolan contains geometric concepts in the form of right triangles and parallel lines, trigonometric concepts through the comparison of the sides of right triangles, and arithmetic concepts in the form of size patterns that form arithmetic sequences in the variations of the length of the handle, barrel, and barrel. These findings indicate that traditional games based on simple constructions can be used as a context for mathematics learning, particularly in geometry, trigonometry, and arithmetic.